Could Postmortem Iss and Niss Points Sign Preventable Deaths - Toka, Hakan; Karbeyaz, Kenan; Gündüz, Tarık; Balcı, Yasemin (The Bulletin of Legal Medicine, 2010)
Many physiological and anatomical scoring systems have been developed for the evaluation of traumatic patients. The most commonly used anatomical scoring systems are the Abbreviated Injury Scale (AIS) and Injury Severity Score (ISS), its derivatives. In 1997, ISS has been modified as the New Injury Severity Score (NISS) by Ossler et al. In this study, it was aimed to evaluate the ISS and NISS scores according to the autopsy findings of the trauma cases. Between 2001-2007,157 cases of traumatic excess deaths and its autopsies were respectively evaluated in the light of the AIS scores, ISS and the NISS values of wounds at the Osmangazi University Faculty of Medicine Department of Forensic Medicine. There were available 67.5% of penetrated injuries and 32.5% of blunt injuries in the cases. The number of cases both the ISS and NISS values is 14 and below was 12 (7.6%). In the group of penetrating injuries, the number of the cases both ISS and NISS values 75 were found statistically higher than in the group with blunt injuries. Although in blunt injury group ISS and NISS values were low the number of cases resulting in death were found to be statistically more than penetrating injuries. In the cases with ISS values less than 50, the rate of multiple wounds in head-neck and chest is more than according to in the cases with ISS values more than 50. In 29 of 157 cases (18.5%), the NISS value were taking place in higher group than ISS value. The ISS and NISS is thought to be insufficient to determine preventable deaths, if physiological mechanisms having role in a person's death and blunt injuries, which are cannot be demonstrated anatomically, with multiple injuries in the same body and in cases with the possibility of complications hospital inpatient treatment for a while so obvious infection etc. In addition, in the forensic deaths, injury time, the period between injury and death, unknown duration of first aid and transporting to the hospital are affecting factors the reliability of such these studies.Key words: Preventable death, autopsy, trauma score, ISS, NISS
Keywords: preventable death; autopsy; trauma score; iss; niss